PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 TERHADAP HASIL BELAJAR IPAS MATERI PERKEMBANGBIAKAN TUMBUHAN KELAS IV SD NEGERI GIYONO KABUPATEN TEMANGGUNG - Fianto, Netta Adella; Mulyani, Petra Kristi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT ABSTRACT Education is a conscious human effort to increase knowledge that is useful for developing intelligence and human resource potential. In its implementation, learning media are needed to support the learning process in the classroom. According to students, classroom learning during science subjects has not been able to utilize learning media effectively, resulting in a lack of student interest in learning, resulting in low learning outcomes. The purpose of this study was to develop the Articulate Storyline 3 learning media for plant propagation to improve learning outcomes for sixth-grade elementary school students. The research location was Giyono State Elementary School in Temanggung Regency. The Research and Development (R&D) method was used in the study, and the ADDIE model was used. The ADDIE model includes the stages of analysis, design, development, implementation, and evaluation. The methods used in data collection were observation, interviews, tests, and questionnaires. The data analysis techniques used in this study were qualitative descriptive analysis, quantitative analysis, and inferential statistics. The subjects in the study were students, teachers, media experts, and material experts. The result of the media development is a website-based interactive application containing complete plant propagation material, equipped with propagation process material, illustrative videos, interactive quizzes, and direct feedback for students. The validation results show that this media received a very decent score from all validators: media experts gave a score of 94% reflecting the excellent quality of the media's display, navigation, and interactivity; material experts gave a score of 87% indicating the accuracy and suitability of the plant propagation material content with the Independent Curriculum; and class teachers gave a score of 88.75% indicating ease of use and suitability of the media to learning needs. The results of the trial on students showed a significant increase in learning outcomes, where the average pretest score for the small group was 52.47 and the large group was 55.71 which was originally below the Minimum Competency (KKM) increased drastically to 89.12 and 88.47 in the posttest after using the media. This improvement was confirmed through the N-Gain test, with values ​​of 0.782 (small group) and 0.736 (large group), both of which fall into the high category. The t-test yielded a 2-tailed value of 0.000 < 0.05, indicating a highly significant difference in learning outcomes before and after media use. Thus, the developed Articulate Storyline 3 learning media is feasible and effective for use in the science learning process to improve student learning outcomes.